Collaboration between local social policy entities and their readiness to implement social innovations - Kretek-Kamińska, Agnieszka; Zajda, Katarzyna (Research Papers of Wrocław University of Economics, 2018)
The aims of the article are: 1) to present the extent of collaboration between different local social policy entities located in 29 rural communes of Łódzkie Province, 2) to analyze these entities’ readiness to implement social innovations, 3) to verify the relationship between non-governmental organizations’ potential to collaborate with other entities of local social policy and their readiness to implement social innovations. The results of the presented research show that in the studied rural communes non-governmental organizations are not considered by communal offices as true partners equally responsible for the implementation of the local social policy. NGOs’ readiness to implement social innovations is related to openness to cross-sectoral collaboration and assuming the role of real partners in this collaboration
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2018, Nr 510, s. 102-110
Keywords: local social policy entities; social innovations; collaboration; public institutions; non-governmental organizations; podmioty lokalnej polityki społecznej; innowacje społeczne; współpraca